DETERMINAN PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH BUKU 2 TAHUN 2017-2020 - Rusdi Bahalwan; Edi Muhammad Jayadi; Muhamad Yusup; Herawati Khotmi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Mudharabah financing is the first financing introduced in Islamic banking. It is a collaboration between the owner of capital and the manager with the distribution of profits according to mutual agreement. Ways to measure the performance of Islamic banking are by looking at the value of CAR, FDR, TPF, and ROA. This study aims to examine the effect of CAR, FDR, TPF & ROA partially on mudharabah financing at Islamic Commercial Banks in Book 2 for the 2017-2020 period and to examine the effect of CAR, FDR, DPK & ROA simultaneously on the financing. This research is quantitative where the population is the Islamic commercial Bank in Book 2 and the samples are 4 banks using quarterly financial reports so that the sample of this study is 64. The analysis used is the Classical Assumption test and then the Hypothesis test data processing assisted with SPSS. The results of the study indicate that CAR & TPF positively affect mudharabah financing and FDR & ROA have no effect on the financing. Meanwhile, CAR, FDR, TPF, ROA altogether have a positive effect on it.